Issuance of corporate bonds – benefits for issuers and investors (Economic and Political Thought, 2018)
A comment is made in the introduction to the article that the low rateof investment observed for years and being far below the EU average is themain barrier to the development of Poland’s economy. The author believesthat this disadvantageous trend may change as a result of the debt instrumentsmarket ‘Catalyst’ established in 2009. With the Catalyst market, on theone hand, an opportunity for development of funding economic undertakingswith the use of bonds and, on the other hand, favourable and flexible investmentof financial means in debt securities by a bigger number of corporateand individual investors emerged. In the article, attention is focused on corporatebonds, which, in the author’s opinion, due to advantages presented inthe article, may constitute the most flexible and efficient source of fundingbusinesses, which is an alternative to a bank debt.
Keywords: corporate bonds, European Union, investment, Polish economy, bank